2007
DOI: 10.1021/jp067278j
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium vs Ground-State Planarity of the CONH Linkage

Abstract: Planarity of the XC(d)NHY linkage has been investigated in unprecedented detail in a number of relatively simple compounds, including formamide (, and methyl carbamate (X ) OCH 3 , Y ) H). Reliable estimates of the equilibrium structures of formamide, cyanamide, acetamide, urea, carbamic acid, methylamine, dimethyl ether, and methyl carbamate are derived, mostly for the first time. It is shown that formamide, considered prototypical for the amide linkage, is not typical as it has a planar equilibrium amide lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
82
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 92 publications
5
82
1
Order By: Relevance
“…Table 4 shows that the calculation using B3LYP/cc-pVDZ with an anharmonic approximation was in general adequate to reproduce the experimental values of the vibrational frequencies and the intensities of methylcarbamate. However, the assignment of vibrations at medium and low frequencies did not always agree with the literature [13,18]. Thus, it should be noted that our quantum-chemical calculations predicted significant delocalization of the urethane vibrations.…”
contrasting
confidence: 72%
See 3 more Smart Citations
“…Table 4 shows that the calculation using B3LYP/cc-pVDZ with an anharmonic approximation was in general adequate to reproduce the experimental values of the vibrational frequencies and the intensities of methylcarbamate. However, the assignment of vibrations at medium and low frequencies did not always agree with the literature [13,18]. Thus, it should be noted that our quantum-chemical calculations predicted significant delocalization of the urethane vibrations.…”
contrasting
confidence: 72%
“…The molecular fragment is delocalized. The average value of the corresponding dipole-moment component is equal to zero [13]. A calculation of a system of inversion states [14] confirmed such a point of view.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…First, it is one of the best models of the peptide bond; secondly, there is the question of whether or not the arrangement of the bonds around the nitrogen atom is planar or pyramidal, the question being common to other nitrogen-containing molecules such as amines, amides, and nitro molecules; [4] thirdly, pyramidization aside, there is the question of the planarity of the heavy atom framework C(CO)N; [5] furthermore, the rotation of the methyl group leads to three conformers; [4] and finally the low methyl rotation barrier leads to an ambiguity of nonplanar equilibrium structures versus an effective planar ground state. [6] Demaison et al [6] made an extensive study of the planarity of the CONH linkage in formamide, cyanamide, acetamide, urea, carbamic acid, methylamine, dimethyl ether, and methyl carbamate. They concluded that the CONH linkage is quite complex.…”
Section: Introductionmentioning
confidence: 99%